Answer:
(2x-9)(2x+9)
Step-by-step explanation:
This is a difference of squares because it can be written as (2x)^2-9^2
The formula for factoring a difference of squares is a^2-b^2=(a-b)(a+b)
So replace a with 2x and b with 9 giving us
4x^2-81=(2x-9)(2x+9)
Answer: I need help too
Step-by-step explanation:
I think is -6
Answer:
The answer to your question is the third choice
Step-by-step explanation:
To solve this problem, just multiply 6 by each of the numbers of the matrix and simplify.
6 | 4 -2 1 | = | (6 x 4) (6 x -2) (6 x 1) |
| 7 3 0| | (6 x 7) (6 x 3) (6 x 0) |
= | 24 -12 6 |
| 42 18 0 |
The first choice is wrong because only multiply by six the first row.
The second and fourth rows are incomplete.
Answer:
$1.25
Step-by-step explanation:
0.35 x 8 = 2.80
7.20 + 2.80 = 10
10 divided by 8 = 1.25
Thank you :)